(untitled) (Research Nepal Journal of Development Studies, 2025)
Tourism based on Gandhian philosophy is Gandhian Tourism is based on regenerative tourism of 21 century. The philosophy is directly related to the sustainable regenerative responsible tourism in global perspective. In Nepal, the tourism sector, welcoming over 1.15 million international visitors in 2025 and contributing approximately 7-8% to gross domestic product while supporting more than one million jobs, predominantly in rural Himalayan regions. The rural tourism copes with deep-rooted economic leakage of 70-90% and rising carbon emissions from aviation and mechanized trekking. This research pioneers Gandhian tourism, adapting Mahatma Gandhi’s tenets of Swadeshi (self-reliance) and Gramswaraj (village autonomy) to foster decentralized, community-driven rural tourism models that emphasize local sourcing, artisan-led experiences, and minimal-import homestays. Through a mixed-methods framework, including expenditure multipliers, input-output analysis, and life-cycle carbon evaluations, the study compares three Gandhian-inspired villages with three conventional ones in Mustang, Ghandruk and Saurah regions. Results demonstrate that Gandhian models retain 75-85% of revenues locally, reducing leakage by 20-30%, and limit per-tourist-day emissions by 25-35% via reduced mechanization and eco-practices. These outcomes advance equitable carbon distribution, strengthening rural resilience and aligning with Sustainable Development Goals 8, 12, and 13, urging policy shifts toward incentivized village-led tourism for Nepal’s sustainable future.